Strategi Pemberdayaan Usaha Mikro Kecil dan Menengah UKM Center Fakultas Ekonomi Universitas Indonesia - Nufus, Belgis Hayyinatun; Saraswati, Kania (Jurnal Ilmu Kesejahteraan Sosial, 2014)
This article describes the develpoment strategy of micro, Small and medium enterprises which was done by UKM center Economy Faculty of Indonesia University. This study used qualitatve research with descriptive design. while colecting data used study literature, in-dept interview and observation with purposive sampling techincal. The result of this study discusses that development strategy of micro, small and medium enterprises which was done by UKM Center there were two strategy, that are : giving